Respuesta :
Answer:
The answer to your question is x = x
Step-by-step explanation:
-2(x + 6) + 6x = 4(x - 3)
Process
1.- Expand
-2x - 12 + 6x = 4x - 12
2.- Simplify
4x - 12 = 4x - 12
3.- Add 12 in both sides
4x - 12 + 12 = 4x - 12 + 12
4.- Simplify
4x = 4x
5.- Divide by 4 both sides
4x/4 = 4x/4
6.- Simplify
x = x
Answer:
any value of x will satisfy this equation
Step-by-step explanation:
The equation can be simplified to ...
-2x -12 +6x = 4x -12 . . . . . .eliminate parentheses; next, collect terms
4x -12 = 4x -12 . . . . . . . . . . true for any value of x
The equation has an infinite number of solutions: x may be any value.